A cost-effectiveness analysis of pneumococcal conjugate vaccines in infants and herd protection in older adults in Colombia - Jaime E. Ordóñez; Angélica Ordóñez (Taylor & Francis Group, 2023)
Background Pneumococcal diseases have a clinical and economic impact on the population. Until this year, a 10-valent pneumococcal vaccine (PCV10) used to be applied in Colombia, which does not contain serotypes 19A, 3, and 6A, the most prevalent in the country. Therefore, we aimed to assess the cost-effectiveness of the shift to the 13-valent pneumococcal vaccine (PCV13). Research design and methods A decision model was used for newborns in Colombia between 2022-2025 and adults over 65 years. The time horizon was life expectancy. Outcomes are Invasive Pneumococcal Diseases (IPD), Community-Acquired Pneumonia (CAP), Acute Otitis Media (AOM), their sequelae, Life Gained Years (LYGs), and herd effect in older adults. Results PCV10 covers 4.27% of serotypes in the country, while PCV13 covers 64.4%. PCV13 would avoid in children 796 cases of IPD, 19,365 of CAP, 1,399 deaths, and generate 44,204 additional LYGs, as well as 9,101 cases of AOM, 13 cases of neuromotor disability and 428 cochlear implants versus PCV10. In older adults, PCV13 would avoid 993 cases of IPD and 17,245 of CAP, versus PCV10. PCV13 saves $51.4 million. The decision model shows robustness in the sensitivity analysis. Conclusion PCV13 is a cost-saving strategy versus PCV10 to avoid pneumococcal diseases.